Protective effect of anti-erosive solutions enhanced by an aminomethacrylate copolymer - Augusto, Marina Gullo [UNESP]; da Silva, Luis Felipe Oliveira [UNESP]; Scaramucci, Tais; Aoki, Idalina Vieira; Torres, Carlos Rocha Gomes [UNESP]; Borges, Alessandra Bühler [UNESP] (Elsevier, 2021)
OBJECTIVE: To investigate if an aminomethacrylate copolymer (AMC) could potentiate the anti-erosive effect of solutions containing sodium fluoride -F (225 ppm F-) and sodium fluoride associated to stannous chloride -FS (800 ppm Sn2+). METHODS: The experimental solutions (F, FS, AMC, AMC + F, AMC + FS, and deionized water-DW as negative control) were tested in the presence of acquired pellicle. Polished bovine enamel specimens (n = 13/group) were submitted to an erosion-rehardening cycle (2 h immersion in human saliva, 5 min in 0.3 % citric acid, 1 h in human saliva, 4×/day, 5 days). Treatment with the solutions was performed for 2 min, 2×/day. The rehardening (%Re) and protective (%Prot) potential of the solutions were assessed in the beginning of the experiment, and the surface loss (SL) by contact profilometry after 5 days. Additional bovine specimens (n = 5/group) were prepared to evaluate the contact angle on the treated enamel surface. The zeta potential of the dispersed hydroxyapatite (HA) crystals after the treatment with the solutions was also measured (n = 3/group). Data were statistically analyzed (α = 0.05). RESULTS: The association with AMC improved the %Re and the %Prot for W and F, but not for FS. The results of SL were: AMC + F = AMC + FS < AMC < FS < F < DW. The presence of AMC significantly reduced the contact angle on enamel surfaces. The HA presented a strong negative surface charge after the treatment with DW, F and FS, whereas after the treatment with the solutions containing AMC it became positive. CONCLUSION: AMC has potential to enhance the anti-erosive effect of fluoride solutions. CLINICAL SIGNIFICANCE: The aminomethacrylate copolymer (AMC) may be a promising agent to be added to oral care products for the prevention of erosive tooth wear.
Keywords: Dental enamel; Dental erosion; Polymers; Sodium fluoride; Stannous chloride